AN INVESTIGATION OF THE PSYCHOLOGICAL AND SOCIAL EFFECTS OF THE COVID-19 PANDEMIC IN THE CONTEXT OF SOCIAL POLICY (Third Sector Social Economic Review, 2023)
The Covid-19 pandemic has plunged humanity into a deep sense of fear and anxiety. Humanity has been faced with a deadly global epidemic that is very difficult to control with current life practices and has a high rate of contagion. Epidemics that affect people and society in many ways are biological, psychological and socio-economic phenomena that can cause structural and functional changes. It is aimed to reveal solution policies against social effects. Within the framework of this purpose, scans were made in the library and internet environment with the key concepts of ""Covid-19"", ""psychological and social effects"". As a result of this scanning, articles, theses and books that were found suitable for the purpose were examined. At the end of the research in which descriptive analysis was used; Within the framework of the measures taken with the Covid-19 epidemic, the social effects were discussed and analyzed in the context of social policy. In the light of today's dynamics, there is a Momentum Movement in terms of the revival, globalization and rise of human values, universal norms and values (for example: the feeling of compassion). Humanity regains self-awareness towards human and nature and to behave respectfully and responsibly towards natural values; for a world order worthy of human dignity and values, there is a need for a new renaissance in which people recourse to their originality.
Keywords: Covid-19 pandemic; social impact; social policy; isolation; restriction